Meningkatkan Kemampuan Memotong Kuku Melalui Strategi Direct Instruction Bagi Anak Tunagrahita Ringan di Kelas IV SLB YAPPAT - Anggraini, Silvia; Kasiyati, Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2021)
The purpose of this study is to prove an effective direct instruction strategy for children's independence in cutting nails for children with mild retardation. The method used in this study is the Single Subject Research (SSR) method with the design A-B-A. baseline condition (A1) is an initial condition consisting of 4 meetings until the data is stable. Condition (B) is an intervention consisting of 7 meetings until the data is stable, and baseline (A2) is a condition after no longer given intervention consisting of 5 meetings. Data collection techniques are used by means of observation, documentation and tests. The results of the study showed that direct instruction strategies can increase self-reliance in cutting nails for children with mild retardation.